Gastrointestinal Presentation in COVID-19 in Indonesia: A Case Report - Muhammad Khifzhon Azwar; Fauzia Kirana; Adi Kurniawan; Sri Handayani; Siti Setiati (Interna Publishing, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently causing a widespread infection in the world. During the pandemic, physicians may need to raise the index of suspicion earlier in at-risk patients presenting with gastrointestinal symptoms, which are uncommon findings in coronavirus disease 2019 (COVID-19) patients. We report a patient in Indonesia with chest pain and gastrointestinal symptoms who was later confirmed to have SARS-CoV-2 infection after spending days of hospitalisation in the standard ward.